OP0264 Relative Frequencies of Circulating T Follicular Helper and T Follicular Regulatory Cells in Autoimmune Patients and Healthy Control Donors and The Effect of Disease Modulating Therapy. (15th July 2016) - Macdonald, A.J.; Cerosaletti, K.; Chen, J.; Nguyen, T.-S.; Posso, S.; Marchesini, G.; Abashian, M.; Martin, A.P.; De Rosa, D.; Samanta, T.; Poorbaugh, J.; Benschop, R.J.; et al.
Abstract : Background: T follicular helper cells are critical in the formation of autoantibody-producing ectopic germinal centers in seropositive autoimmune diseases and have attracted interest as potential biomarkers of autoimmune disease activity. A further subset with regulatory properties (Tfr) has also been described but, as yet, not well characterized in autoimmune diseases. Objectives: The purpose of this study was to (1) determine the frequencies of Tfh in a range of autoimmune diseases by flow cytometry and a new commercially available Tfh epigenetic marker assay, (2) ascertain if Tfr frequencies vary among AI diseases, (3) determine effect of treatment on Tfh/Tfr frequencies in the autoimmune groups. Methods: Patients were recruited from the Rheumatology or Neurology clinics at the Virginia Mason Clinic in Seattle WA. Healthy controls were recruited from the Seattle community. AI samples were selected regardless of length of disease or therapy; healthy control samples were matched with AI samples for age, gender and race. Cryopreserved peripheral blood mononuclear cells (PBMC) from 50 each of systemic lupus erythematosus (SLE), systemic sclerosis (SSc), multiple sclerosis (MS), rheumatoid arthritis (RA) and healthy volunteers (HV) were analyzed by multicolor flow cytometry for Tfh and Tfr frequencies. Tfh frequencies were also analyzed by a PCR-based assay from Epiontis GmbH, Germany. Initial experiments established that results obtained from fresh versus frozen PBMC were not significantly different. Relative frequencies of Tfh and Tfr were compared among disease/control groups, and in relation to disease activity and concurrent therapies – none, DMARDs, depleting (biologics, Cytoxan, MMF) Results: Elevated frequencies of Tfh were seen in SSc, MS and RA compared with healthy controls, but not in SLE. TFh counts by flow cytometry and Epiontis epigenetic assay were significantly correlated within groups and globally. Tfr percentages were increased in RA, SSc and SLE compared with healthy controls, and the ratio of Tfh/Tfr was reduced in SLE compared with the other study groups. Tfh frequencies were positively correlated with inflammation (ESR) in SLE. Depleting therapy reduced Tfh and/or Tfr frequencies in patients with SLE and SSc. Conclusions: A novel epigenetic marker assay to count Tfh proved to be robust and correlated well with flow cytometry counts. This supports the use of the PCR-based epigenetic marker assay as a replacement for multi-color flow cytometry. This would facilitate standardization of Tfh counts in clinical trials and studies where multiple sites are involved. A range of Tfh and Tfr frequencies were observed in the peripheral blood of patients with autoimmunity, but levels were significantly elevated in SSc, MS and RA patients. In SLE patients, Tfh levels correlated with ESR values and may be indicative of ongoing inflammation. Tfh and/or Tfr levels in SLE and SSc may be modulated though the use of biologics or cytotoxic therapies and further longitudinal studies are indicated. Disclosure of Interest: None declared